Improvement of sludge characteristics and mitigation of membrane fouling in the treatment of pesticide wastewater by electrochemical anaerobic membrane bioreactor. (15th April 2022) - Hu, Dongxue; Liu, Lixue; Liu, Wenyu; Yu, Liqiang; Dong, Jian; Han, Fei; Wang, Hongcheng; Chen, Zhaobo; Ge, Hui; Jiang, Bei; Wang, Xin; Cui, Yubo; et al.
Highlights: A novel reactor was designed to treat pesticide wastewater efficiently. The sludge yield was reduced by 41.2 ± 6.7% and the SVI was decreased by 32.5±13.8%. The methane yield was increased by 34.4 ± 17.4% to achieve higher energy recovery. Membrane fouling resistance was reduced and fouling rate was delayed by 31.0–38.5%. The correlations of membrane fouling and EPS content and SVI were expounded. Abstract: Electrochemical anaerobic membrane bioreactor attracted attention due to stable treatment quality with low footprint, and draw solute has significant effect on the sludge characteristics and membrane fouling performance. In this pilot-scale study, an electrochemical anaerobic membrane bioreactor (E-AnMBR) was proposed for treating pesticide wastewater at different hydraulic retention times (HRTs), demonstrating that E-AnMBR was superior on improvement of sludge characteristics and mitigation of membrane fouling, compared with the conventional anaerobic membrane bioreactor (C-AnMBR). E-AnMBR reduced sludge yield by 41.2 ± 6.7% and the SVI was significantly decreased by 32.5±13.8%. The accumulation of VFA in E-AnMBR was slighter than that of C-AnMBR, and the minimum average VFA was 255±6 mg/L. The methane yield of E-AnMBR (0.22–0.29 L CH4 /g CODremoved ) was 1.2–1.4 times than that of C-AnMBR. The EPS contents in suspended and attached sludge of E-AnMBR were significantly reduced by 41.8 ± 3.3% and 77.4 ± 14.5% than that of C-AnMBR, respectively. These results suggested that E-AnMBR has lower sludge disposal pressure, higher stability and methane recovery potential. Not only that, E-AnMBR successfully reduced membrane resistance, delaying the fouling rate by 31.0–38.5%. Finally, the linear relationship between EPS characteristics and membrane pollution was determined. Graphical abstract: Image, graphical abstract